ARGUING THE JUST WAR IN ISLAM - John Kelsay; Reviewed by: Ridwan Rosdiawan (Al-Albab, 2013)
One of the magnitude effect of the horrific 9/11 terrorist attacks on the United States and the subsequent war against terror campaign is a political rhetoric that divides the international world into two rigid poles,” the evil terrorist” in one side and the “righteous, just enlightened victim” in the other. The United States administration has succeeded in placing itself as the protagonist side and its rally for retaliatory war campaign has not only gained international support but also affirmed its position as the leader of the ‘the key-holder of freedom, liberty and humanity’, who waged war against the barbaric evil terrorists. By calling ‘either with us or against us’, the US leaves no room for the rests of the world to be in ‘grey’ area. Those who are not in favor will be considered as enemy and therefore deserve to be punished.